Screening and management of pre-eclampsia and eclampsia in antenatal and labor and delivery services: findings from cross-sectional observation studies in six sub-Saharan African countries - Barbara Rawlins; Marya Plotkin; Jean Pierre Rakotovao; Ashebir Getachew; Maria Vaz; Jim Ricca; Pam Lynam; Frank Kagema; Patricia Gomez (BMC, 2018)
Abstract Background Preeclampsia and eclampsia (PE/E) are major contributors to maternal and neonatal deaths in developing countries, associated with 10-15% of direct maternal deaths and nearly a quarter of stillbirths and newborn deaths, many of which are preventable with improved care. We present results related to WHO-recommended interventions for screening and management of PE/E during antenatal care (ANC) and labor and delivery (L & D) from a study conducted in six sub-Saharan African countries. Methods From 2010 to 2012, cross-sectional studies which directly observed provision of ANC and L & D services in six sub-Saharan African countries were conducted. Results from 643 health facilities of different levels in Ethiopia (n = 19), Kenya (n = 509), Madagascar (n = 36), Mozambique (n = 46), Rwanda (n = 72), and Tanzania (n = 52), were combined for this analysis. While studies were sampled separately in each country, all used standardized observation checklists and inventory assessment tools. Results 2920 women receiving ANC and 2689 women in L & D were observed. Thirty-nine percent of ANC clients were asked about PE/E danger signs, and 68% had their blood pressure (BP) taken correctly (range 48-96%). Roughly half (46%) underwent testing for proteinuria. Twenty-three percent of women in L & D were asked about PE/E danger signs (range 11-34%); 77% had their BP checked upon admission (range 59-85%); and 6% had testing for proteinuria. Twenty-five cases of severe PE/E were observed: magnesium sulfate (MgSO4) was used in 15, not used in 5, and for 5 use was unknown. The availability of MgSO4 in L & D varied from 16% in Ethiopia to 100% in Mozambique. Conclusions Observed ANC consultations and L & D cases showed low use of WHO-recommended practices for PE/E screening and management. Availability of MgSO4 was low in multiple countries, though it was on the essential drug list of all surveyed countries. Country programs are encouraged to address gaps in screening and management of PE/E in ANC and L & D to contribute to lower maternal and perinatal mortality.